A Scalable Mechanism Based on Blockchain for Information Processing in Energy Trading - Xunyan Jiang; Lei Wu (Discrete Dynamics in Nature and Society)
Energy Internet (EI) can provide a fair, transparent, and safe environment for the energy market through the rational use of the Internet and blockchain technology. However, the existing EI has complicated management in energy, capital, and information flow. Furthermore, blockchain technology (BT) is a new technique with a scalability problem. To overcome the problem, we proposed a scalable mechanism based on blockchain for information processing in energy trading. The proposed mechanism adopts three-way communication (TWC) between energy utilities and consumers to effectively manage the energy, capital, and information flow. In the running of TWC, three modules of BT-based Internet of Things (IoT) system, BT-based virtual currency system, and BT-based EI information platform are constructed. In addition, we proposed that these modules are managed by carrying out weak centralized management to make the EI system scalable. In the operation of this mechanism, the functions of the three modules are independent and parallel. The proposed mechanism can realize the efficient transmission of energy and information and help to solve the supervision problem of energy trading. Compared with the existing information process mechanism, it is superior in promoting the dynamic balance of resources in a wide range and meeting the fast, efficient, and safe energy trade needs between the supply and demand sides.